Job satisfaction within construction sector employees: case study of M.M.Shawl Engineers& Contractors Pvt Ltd - Rafiqi, Haris Altaf (2019)
As per Mitchell, employees that quit from an organization after they learn all the tricks of the trade, take away all the necessary skill set and knowledge acquired from the organization, thus the replacement cost of such a worker is equal to two times an individual’s yearly income ( BEHERA, C.SAHOO and B.Sundaray, 2011). The new replacement employee requires training in order to inculcate him with necessary skills so that he performs at a desired level, which means that the organization has to invest resources such as time, capital on the new recruit (BEHERA, C.SAHOO and B.Sundaray, 2011). In this research we are going through case study of M.M.SHAWL ENGINEERS & CONTRACTORS PVT LTD, which is an Indian local construction company. The sole aim of this research is to understand how satisfied construction industry workforces are in their respective professions and to bring to the attention of the construction companies, areas which require immediate attention in order to have motivated and satisfied workforce.